Analysis of Three Tensions in Real Estate Companies in Indonesia (PT XYZ Case Study) - Pratama Yudhistira, Ary (Green Publisher Indonesia, 2025)
This study aims to measure the management of three tensions in a company. This research was conducted at a real estate company that has been listed on the Indonesia Stock Exchange, namely PT XYZ. Data is obtained through financial data (in the form of audited financial statements for the period 2019 to 2021). The data obtained was then analyzed using a qualitative descriptive analysis approach. The framework in this study is divided into three tensions, namely profitability vs growth, today vs tomorrow, and whole vs parts. To analyze the data needed in this study, researchers used the batting average technique for each tension. Significant findings are found in the whole vs parts tension with a batting average score of 100% while for the other tensions, namely profitability vs growth and today vs tomorrow, each is only 33%. These findings are useful as a source of input for companies and interested parties in encouraging improved financial management and company resources in the future.